2010
DOI: 10.1016/j.jhazmat.2009.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between disintegrated and fermented sewage sludge for production of a carbon source suitable for biological nutrient removal

Abstract: There is a need to investigate processes that enable sludge re-use while enhancing sewage treatment efficiency. Mechanically disintegrated thickened surplus activated sludge (SAS) and fermented primary sludge were compared for their capacity to produce a carbon source suitable for BNR by completing nutrient removal predictive tests. Mechanically disintegration of SAS using a deflaker enhanced volatile fatty acids (VFAs) content from 92 to 374 mg l(-1) (4.1-fold increase). In comparison, primary sludge fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 31 publications
2
50
1
Order By: Relevance
“…With WO material little difference was observed when changing from a low to high background of primary wastewater, which would support the notion that WO liquor has a greater mixture of carbon compounds (and/or nutrients or trace elements) and the increase in background carbon made little difference with this supplement. Other studies had indicated that complex substrates and mixture of VFAs from solubilised sludge stimulated higher denitrification rates than just acetate (Kampas et al, 2009;Soares et al, 2010). Kristensen and Jørgensen (1990) had also observed similar denitrification rates when supplementing with acetate or biologically hydrolysed sludge.…”
Section: Comparing Denitrification From Different Full-scale Wwtp Actmentioning
confidence: 93%
See 1 more Smart Citation
“…With WO material little difference was observed when changing from a low to high background of primary wastewater, which would support the notion that WO liquor has a greater mixture of carbon compounds (and/or nutrients or trace elements) and the increase in background carbon made little difference with this supplement. Other studies had indicated that complex substrates and mixture of VFAs from solubilised sludge stimulated higher denitrification rates than just acetate (Kampas et al, 2009;Soares et al, 2010). Kristensen and Jørgensen (1990) had also observed similar denitrification rates when supplementing with acetate or biologically hydrolysed sludge.…”
Section: Comparing Denitrification From Different Full-scale Wwtp Actmentioning
confidence: 93%
“…In this manner the WO material could be ranked in terms of known carbon sources. The batch assay allowed for higher throughput and required smaller volumes than a full SBR study and was modelled upon work by Kampas et al (2009);Kampas (2007) and Soares et al (2010). Biomass from each of the five parent reactors was centrifuged at 2000 rpm for 1 min in a swing head centrifuge (International Equipment Company, Biolab Scientific Ltd.), washed with fresh media (10% wastewater diluted with water containing phosphate buffer at 20 mM at pH 7.5, 30 mg/l CaCO 3 , 75 mg/l CaCl 2 Á 2H 2 O, 100 mg/l MgCl 2 Á 6H 2 O) and then resuspended in the media.…”
Section: Batch Assays To Determine Denitrification After Acclimation mentioning
confidence: 99%
“…An increased concentration of organic and inorganic substances in post-digestion waters undergoing pre-treatment influenced also the sludge susceptibility to dewatering in a negative way (Table 5). Such liquors exhibited a negative impact on the wastewater treatment processes, especially the denitrification [34,35]. Nowadays, the post-digestion liquors are more and more frequently treated separately with the application of biological as well as physical and chemical methods.…”
Section: Sludge Dewatering and Characteristics Of Post-digestion Watersmentioning
confidence: 99%
“…15-0.20), which has a negative impact on the wastewater treatment process, especially on the denitrifi cation. Their treatment in such way requires the addition of external carbon source [19,35].…”
Section: Introductionmentioning
confidence: 99%